China's evolving green planning system: Are targets the answer? - Genia Kostka (Frankfurt School of Finance & Management, 2013)
China's national leaders have recently set ambitious goals to restructure and diversify the economy towards a more resource-efficient and sustainable growth path. To address the growing national environment and energy concerns, leaders introduced several binding environmental targets for government departments and large enterprises. The heavy reliance on a target-based implementation approach raises questions about the effectiveness of this strategy in the short and long run for environmental governance in China. Based on fieldwork in Jiangsu, Hunan, and Shandong provinces in 2012, this paper studies the desirable and undesirable outcomes of binding environmental targets in China's evolving green planning system. This paper argues that environmental targets have a signaling function that has resulted in ecological issues movement onto local governments' core policy agendas. However, in the nascent green planning system, classic planning problems have generated undesirable consequences such that that environmental targets are not always achieving their intended goals. Strategic and cyclical behavior by local government officials in leadership positions often lead to short-term maximization actions instead of long-term innovative environmental management. This analysis of local leaders' responses to top-down targets aims to generate a more realistic picture of what binding environmental targets can and cannot achieve.
Keywords: Q48; Q28; Q00; P21; O21; R58; 330; environmental policy implementation; regulation; command and control instruments; targets; China; authoritarian environmentalism